The Role of Social Sciences in Addressing Contemporary Issues in Islam - Hatta, Jauhar; Aulia, Muhammad Ghozil (AN NUR: Jurnal Studi Islam, 2025)
This study aims to analyze how social sciences can inform social policies that align with the principles of Islamic teachings, with a focus on Islamic studies. Using a qualitative approach with a literature review method, this research examines various relevant literature on the integration of social sciences, such as sociology and anthropology, with Islamic values. The analysis focuses on social theories that can be adapted to the context of social policy in the Islamic world, as well as how Islamic principles, such as justice, equality, and the welfare of the ummah, can be applied to create more inclusive and sustainable policies. The results of the study indicate that social sciences offer a strong analytical framework for understanding social dynamics in Muslim societies, as well as providing practical insights for formulating policies that integrate Islamic values in addressing contemporary challenges. These findings are expected to serve as a basis for policymakers to design more adaptive social solutions that align with the principles of Islamic teachings.